2018
DOI: 10.1128/jvi.01932-17
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis and Phenotypic Analysis of Mutant Clouds for Hepatitis E Virus Genotype 1

Abstract: Many RNA viruses exist as an ensemble of genetically diverse, replicating populations known as a mutant cloud. The genetic diversity (cloud size) and composition of this mutant cloud may influence several important phenotypic features of the virus, including its replication capacity. We applied a straightforward, bacterium-free approach using error-prone PCR coupled with reverse genetics to generate infectious mutant RNA clouds with various levels of genetic diversity from a genotype 1 strain of hepatitis E vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Sanger sequencing of clones derived from 100 ng 0.2AGCT, 50 ng 0.2 AGCT, and 25 ng 0.2 AGCT libraries showed that the sequences had unique mutations. We had made a similar observation earlier: Sanger sequencing of EP-PCR products that were derived from an HEV cDNA clone had unique mutations (15). Table 1 shows a transition-transversion matrix for genome-wide substitutions for all six libraries.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Sanger sequencing of clones derived from 100 ng 0.2AGCT, 50 ng 0.2 AGCT, and 25 ng 0.2 AGCT libraries showed that the sequences had unique mutations. We had made a similar observation earlier: Sanger sequencing of EP-PCR products that were derived from an HEV cDNA clone had unique mutations (15). Table 1 shows a transition-transversion matrix for genome-wide substitutions for all six libraries.…”
Section: Resultssupporting
confidence: 54%
“…1A, lanes 1 to 4). Previously, we were able to synthesize and diversify the HEV full-length genome of 7.2 kb by reducing the dATP and dGTP concentrations in EP-PCR (15). In this study, we first attempted to further induce genome-wide mutagenesis by reducing both dATP and dGTP concentrations; however, this failed to provide sustained yields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of variants are unable to replicate due to deleterious or lethal effects of the new mutations or are otherwise cleared by the host immune system. However, some variants with beneficial mutations are continuously selected upon due to evolutionary advantages or better adaptation to adverse conditions, such as the presence of a DAA (Agarwal et al, 2018 ; Singh et al, 2020 ). Consequently, natural variants with various levels of susceptibility to DAAs may exist within patients and can be selected after DAA exposure (Ahmed and Felmlee, 2015 ).…”
Section: Hcv Genetic Heterogeneity and The Emergence Of Daa Resistancmentioning
confidence: 99%